SUCCESS FACTORS FOR STRATEGIC ALLIANCES IN THE SOUTH AFRICAN FINANCIAL SERVICES SECTOR - MAINO, LISA COLETTE (My University, 2011)
Strategic alliance activity has grown over the last few decades yet, despite this, the literature reveals a wide acknowledgement that the vast majority of these alliances are plagued by poor performance. In addition to this, despite the extensive literature available on strategic alliances, there does not exist any single integrated theory linking identified success factors into a suitable due diligence investigation framework for a company considering an alliance. This research is therefore a crucial, and long overdue, examination of the many broad and multi-faceted issues affecting strategic alliances, in order to identify the success factors in strategic alliances and to better guide the critical due diligence processes. This study concentrates its findings on South African financial services sector strategic alliance activity. The study examines the rationale behind companies entering into strategic alliances and the types of issues that may arise when contemplating an alliance, to provide these companies with a better understanding of the expected challenges in strategic alliances, in order to assist alliance performance and success. The multi-method approach used includes a comprehensive literature overview, coupled with a review of applicable case studies, and reveals that the key challenges in strategic alliances include, amongst others, issues of partner trust and opportunism, management and leadership issues, strategy issues, people and culture related issues, financial issues and operational issues. The study further reveals that these issues are often largely ignored at alliance formation stage, when in fact these issues are often responsible for the ultimate failure of alliances and should therefore be viewed as success factors key to the success of an alliance. The study therefore translates the key challenges identified as part of the comprehensive literature review into a table of success factors to be considered in strategic alliances by South African companies in the financial services sector. These success factors include, amongst many others, a iv true understanding of the synergy benefits expected from the alliance, the local neighbouring alliance motivators, the political risks and political connections associated with the alliance, as well as the importance of alliance branding, market research, aligning cultures, identifying key employees and implementing succession plans. While these success factors are indeed valuable to any company contemplating an alliance, it is not always clear how to properly investigate these factors with the aim of implementing measures to ensure that these factors become factors of success and not causes of alliance failure. The study therefore recommends ways in which these success factors can be properly interrogated as part of the due diligence investigation, by means of a comprehensive due diligence framework addressing each of the success factors listed under the key challenges identified. The recommended due diligence framework has been divided into mini due diligence investigations to be carried out by the different functions within a company that bear responsibility for the area being investigated and which align to the categories of key challenges identified (for example, the partner, management and leadership, strategy, people and cultural, financial, operational and legal categories), to ensure that a company has comfort that all aspects of the strategic alliance are properly interrogated before the decision to ally is taken by South African companies in the financial services sector
MBA - WBS
Keywords: Strategic alliances; Financial services